Party of the Periphery in the City of the Country’s Center: The Case of the Smer–Social Democracy in Bratislava during Slovakian Parliamentary Elections - Chwedoruk, Rafał; Rydliński, Bartosz (Historia i Polityka, 2025)
The text is devoted to the electoral strongholds of the party Smer–Social Democracy in the Slovak capital. The analyzed party is atypical, as it is strongly anti-establishment and populist left-wing, rarely described in the literature. The research results indicated that a common feature of all Bratislava districts with an overrepresentation of left-wing support in the period in question is their peripheral, outlying location in relation to the capital’s central districts and an above-standard share of 1970s housing.